''Voices of fear'': Latin American terror podcasts for the development of oral expression in higher basic education students - Cabrera-Quirola, Emilia (2025)
The development of oral expression of students in Higher Basic Education continues to be a challenge, since most teachers still use traditional methodologies that do not promote the active participation of students or encourage their creativity. This is crucial because oral expression skills are fundamental to guarantee students' academic, professional and social success. Despite previous efforts using traditional methods such as lectures or reading aloud, it has not been possible to obtain relevant results. Therefore, this study proposes Latin American terror podcasts applied in the educational context as an innovative didactic strategy that contributes to enhance the oral expression of students in Higher Basic Education through a methodology connected to ICTs that encourages their potential. The study was developed through the analysis of the descriptive sample of 1,072 teachers from different educational institutions in Ecuador who participated in the survey of Associated Factors of the evaluation Ser Estudiante 2022-2023 and 24 teachers surveyed by Loja et al. (2020) whose findings show that 62.5% of teachers surveyed do not implement the podcast as part of their strategies in the development of oral expression skills. Thus, it is proposed to implement the Latin American Horror Podcasts as part of the teaching work as a novel strategy, linked to the technological and cultural aspect.